Histomorphological spectrum of uterine leiomyoma and its secondary changes: A retrospective study - Kale, Vidya G; Deore, Bharati S; Nathe, Neha S; Phadol, Jyoti N; Meher, Akshaya P (International journal of health sciences, 2024)
Aim and Background: Leiomyoma is one of the most common causes for abnormal uterine bleeding in females. Furthermore, sometimes leiomyoma is clinically, radiologically, and histologically believed to be malignancy. Thus, there is a need for more studies to know the different variants and secondary changes occurring in leiomyoma. Methods: This study was carried out at the Department of Pathology, Dr. Vasantrao Pawar Medical College, Hospital, and Research Centre. Over a period from January 2019 to June 2023, 355 cases were received and included in this study. The specimen was examined grossly, processed, stained, and studied microscopically. Results: In the current study, cellular leiomyoma was the most common variant and the hyaline degeneration was the most common secondary change identified. Conclusion: The current study gives insights into the clinicopathologic spectrum of uterine leiomyoma along with their clinical presentation, variants and associated secondary changes, in comparison with the findings from similar studies of different areas.